2011
DOI: 10.1093/fampra/cmr016
|View full text |Cite
|
Sign up to set email alerts
|

Patients' hopes and expectations of a specialist chronic fatigue syndrome/ME service: a qualitative study

Abstract: GP referral to a specialist service appeared to be highly valued by the participants in this study. The levels of uncertainty expressed by many patients about the nature of CFS/ME raises the issue of the role of information on CFS/ME during the early stages of the illness and suggests a need for more reassurance and positive advice during the waiting period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The effectiveness of this approach, in conjunction with other factors such as services’ attention to detail around issues such as accessibility and flexibility, would contribute to favourable views of services among patients. ‘Alternative’ approaches to treatment, such as accepting the legitimacy of patients’ accounts of their illness and providing realistic expectations of treatment outcomes [42], have already been adopted, and our study confirms that referral to a specialist service is highly valued [43]. …”
Section: Discussionsupporting
confidence: 70%
“…The effectiveness of this approach, in conjunction with other factors such as services’ attention to detail around issues such as accessibility and flexibility, would contribute to favourable views of services among patients. ‘Alternative’ approaches to treatment, such as accepting the legitimacy of patients’ accounts of their illness and providing realistic expectations of treatment outcomes [42], have already been adopted, and our study confirms that referral to a specialist service is highly valued [43]. …”
Section: Discussionsupporting
confidence: 70%
“… 37 We reported in a previous paper that patients do value referrals, 24 which is in accordance with patients' reports that specialist services provide acknowledgement of their ailments, treatment, better handling of daily life issues and improved dialogue between professionals. 38 However, patients with CFS/ME often have to struggle for a referral, 39 40 which might affect the relationship with their GP. Patients in Europe have evaluated GP care more positively in countries without gatekeeping, 29 and the Norwegian gatekeeping system could explain some of the low primary healthcare scores.…”
Section: Discussionmentioning
confidence: 99%
“…Glynn et al 3 found that two of three patients >50 years of age had multimorbidity, with office visits, hospital admissions and outpatient visits and total health care costs increasing greatly for those with more than four compared to no chronic conditions. McDermott et al 4 found that patients with chronic fatigue syndrome highly valued referral to a specialist service but that they needed more information and reassurance about the condition during the waiting period to be seen there. Vashitz et al 5 found that physicians adhered poorly to guidelines for dyslipidaemia screening and treatment, illustrating the need for more follow-up.…”
Section: A Wide Variety Of Interventions Have Been Testedmentioning
confidence: 99%